The Australian Monstrilloida 3. Caromiobenella Jeon, Lee & Soh, 2018, Monstrilla Dana, 1849, and Sarsimonstrillus n. gen. - Suárez-Morales, Eduardo; Mckinnon, Alexander David (Zootaxa, 2025)
This is the third paper in a series regarding a taxonomical survey of the monstrilloid copepods collected during the past three decades in coastal systems of Australia. The first contribution included the taxonomic analysis of three genera of the Monstrilloida, i.e., Monstrillopsis Sars, 1921, Maemonstrilla Grygier & Ohtsuka, 2008, and the monotypic Australomonstrillopsis Suárez-Morales & McKinnon, 2007. The second document contained the taxonomic analysis of Cymbasoma Thompson, 1888 which emphasized the remarkable diversity of this genus in Australia, with a total of 25 new species. In this third contribution we present an account of the genera Caromiobenella Jeon, Lee & Soh, 2018, and Monstrilla Dana, 1849, and describe a new monotypic genus with paired, anteriorly directed cephalic structures. Thus, the taxonomic account of the monstrilloids found in Australian zooplankton samples collected since 1983 will be completed. Three species of Caromiobenella are reported including an undescribed one. Additionally, this is the first record of C. hamatapex (Grygier & Ohtsuka, 1995) in Australia with a comparative analysis with reports from Japan and South Korea. In this regard, two previous records of Australian Monstrilla and subsequently introduced names assigned to them are both referable to the widespread C. helgolandica (Claus, 1863), a species probably representing a species complex. Furthermore, 11 new species of Monstrilla are described with one species represented by both sexes, eight by only males, and four by only females. A new genus Sarsimonstrillus n. gen. is described from an adult female. Most new species were found in temperate coastal embayments, particularly one with a very rich habitat diversity (Western Port Bay). Only two of the new species of Monstrilla were found in reef-related sites, with one representing a new member of the M. conjunctiva Giesbrecht, 1902 species group. Considering our results of this third contribution, Monstrilla is the second most speciose monstrilloid genus in Australian waters and regains its place as the second most diverse monstrilloid genus worldwide. The summarized contribution of this research initiative (2011–2024) consists of a total of 44 new species and two new genera of the Monstrilloida in Australian waters.